Small and medium enterprises' risk exposures and mitigation approaches in Nigeria - Joshua Solomon Adeyele; Olubunmi Florence Osemene (The Journal of Entrepreneurial Finance (JEF), 2018)
Risks militating against small and medium enterprises (SMEs) have been on the increase due to how risks mitigations are conducted by the owners/operators. Although thorough understanding of businesses undertaken by the owners of SMEs enables them to have a clear picture of risks affecting their businesses so as to act in proactive manner in order to mitigate or avoid the impending risks. To assess the risk exposures of SMEs, a random sampling technique was used to select 209 SMEs within Lagos and Benin City. Both descriptive and inferential statistics such as Phi and Gamma were used to analyse the data collected. The study revealed that the relationship between SMEs' operators understanding of business with risk mitigation, and record backup system are significantly low. However, the understanding is moderately strong with availability of risk management team to mitigate risk after the event (ATE) by the operators of SMEs. The study concluded that SMEs' risk exposures are significant with the operators' understanding of the business which in turn affects how record backup system is maintained and how credit collection strategies are used. Consequently, the study recommended among other things that SMEs' operators need to have thorough understanding of their businesses and they can even hire experts to train them on record backup of vital information of their businesses.
Keywords: D81; L26; 650; SMEs; risk perception; risk exposures; risk mitigation